2009
DOI: 10.1021/jp9017162
|View full text |Cite
|
Sign up to set email alerts
|

SH-Stretching Vibrational Spectra of Ethanethiol and tert-Butylthiol

Abstract: Vibrational spectra of vapor-phase ethanethiol and tert-butylthiol have been recorded in the 1000 to 12,000 cm(-1) region. Both the gauche and trans conformers of ethanethiol are observed. The intensities of SH-stretching vibrations are found to be significantly weaker than the equivalent CH-stretching vibrations and the OH-stretching vibrations in the corresponding alcohols. The relative strength of the SH-stretching vibrations in ethanethiol and tert-butylthiol compared with the OH-stretching vibrations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 73 publications
6
42
0
Order By: Relevance
“…The two overtones 2ν 15 (3) responsible for the separation of the two torsional modes. In particular, these are the A ss coefficient of the (sin 3θ 1 sin 3θ 2 ) term of the PES (6.075 cm −1 ) and the B θ1θ2 kinetic energy parameter (A 00 (B θ1θ2 ) = −0.2971 cm −1 ).…”
Section: Dimethyl-sulfide: Ab Initio Calculations and Fitmentioning
confidence: 99%
See 1 more Smart Citation
“…The two overtones 2ν 15 (3) responsible for the separation of the two torsional modes. In particular, these are the A ss coefficient of the (sin 3θ 1 sin 3θ 2 ) term of the PES (6.075 cm −1 ) and the B θ1θ2 kinetic energy parameter (A 00 (B θ1θ2 ) = −0.2971 cm −1 ).…”
Section: Dimethyl-sulfide: Ab Initio Calculations and Fitmentioning
confidence: 99%
“…12 However, ETSH has been less investigated and a few, generally old information is available. [13][14][15] In 1948, the structure of the two conformers of ethyl mercaptan and the torsional barriers were investigated by Sheppard. 13 In 1968, Smith et al 14 recorded the infrared spectrum of the gauche conformer in gas and condensed phases.…”
Section: Introductionmentioning
confidence: 99%
“…12 In more recent years, XH-stretching transitions of several small molecules including ethylene glycol, peroxynitrous acid, hydroxymethyl hydroperoxide, sulfuric acid, methanesulfonic acid, ethanol, ethanethiol, tert-butanol, and tert-butylthiol have been successfully calculated entirely ab initio with potential energy and dipole moment curves obtained with the CCSD͑T͒ method. [13][14][15][16][17][18][19][20] For many of these systems, a triplecorrelation consistent basis set was pragmatically used as larger basis sets were not considered practicable at the CCSD͑T͒ level of theory.…”
Section: Introductionmentioning
confidence: 99%
“…28 However, based on the Gibbs free energy difference of 1.92 kJ mol −1 between trans and gauche forms, the relative abundances of trans and gauche forms were estimated to be 19% and 81%, respectively. 29 However, conformerspecific ionization spectroscopy studies on ethanethiol revealed only gauche conformer of ethanethiol to be present in a molecular jet. 30 Infrared studies recorded under identical environmental conditions to those used in the present experiment are needed if we are to reveal the nature of ethanethiol molecules formed at 10 K.…”
Section: B Ethanethiolmentioning
confidence: 99%